2000
DOI: 10.1115/1.1343084
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Turbulent Expansion-Corner Flow With Shock Impingement

Abstract: Experiments are performed to study the interaction of an impinging shock wave and an expansion fan in a Mach 1.280 flow. The expansion fan neutralizes the pressure rise induced by the impinging shock wave. The mean surface static pressure shows a linear combination of the effect of both perturbations. Surface pressure fluctuations, which are associated with the characteristics of the perturbed boundary layer, indicate a transitional behavior. This is related to a nonlinear phenomenon arising the simultaneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The wall static pressure showed overshoot compared with inviscid pressure levels and the suppression of SWBLI was experimentally confirmed when the shock impinging point was located downstream of the expansion corner. Chung (2001) investigated a transonic case in which the Mach number was 1.28 and the incident shock impinged exactly at the expansion corner. Wall static pressure measurements for different shock intensities (wedge angles of 1, 3 and 5) and expansion corners (5, 10 and 15) reveal that the downstream peak pressure fluctuation depends on the coupling of the impinging shock and expansion waves.…”
Section: Introductionmentioning
confidence: 99%
“…The wall static pressure showed overshoot compared with inviscid pressure levels and the suppression of SWBLI was experimentally confirmed when the shock impinging point was located downstream of the expansion corner. Chung (2001) investigated a transonic case in which the Mach number was 1.28 and the incident shock impinged exactly at the expansion corner. Wall static pressure measurements for different shock intensities (wedge angles of 1, 3 and 5) and expansion corners (5, 10 and 15) reveal that the downstream peak pressure fluctuation depends on the coupling of the impinging shock and expansion waves.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a reduction in bubble size when its edge is closely located to the corner. Similarly, the effects of expansion corners in the vicinity of SWBLI were considered by few researchers 9–11 . Quan et al 12 experimentally investigated the benefits of installing herringbone riblets at the leading edge of a double wedge structure subjected to Mach 5 flow.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of expansion corners in the vicinity of SWBLI were considered by few researchers. [9][10][11] Quan et al 12 experimentally investigated the benefits of installing herringbone riblets at the leading edge of a double wedge structure subjected to Mach 5 flow. They reported that the expansion waves generated due to the presence of riblets weaken the leading edge shock resulting in less separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computational study of these complex flow-structures is often done using the Reynolds Averaged Navier Stokes (RANS) simulations, owing to its low computation cost [1,2]. Several studies have been conducted to investigate parameters like surface pressure rise, effect of wall temperature [3] in SBLIs with varying conditions and configurations [4,5]. Among these, predictions for SBLIs with strong shock waves have been found unsatisfactory, especially for eddy viscosity based models.…”
mentioning
confidence: 99%